Tectonic evolution of the Changling fault basin and its relationship to oil and gas accumulation - Wang, Jianqiang; Yang, Guang; Xue, Linfu; Zhang, Jianwei; Bai, Ye; Li, Wenbo (Mining science and technology (China), 2011)
The Changling fault depression passed through three stages of evolution： a period of faulting, a period of subsidence, and an inversion period. The fault lifted the whole area and the formation was eroded during the late Yingcheng formation, the late Nenjiang formation, and the late Mingshui formation. The denudation quantity of eight wells located in the study area is estimated by the interval transit time method and by the formation trend extension method using seismic and drilling data. Inversion back stripping tech- nology with de-compaction correction was used to restore the original sedimentary thickness step by step and to recover the burial history at a single well. Two profiles were selected for the recovery and study of the tectonic evolution. The study confirmed that the primary major gas bearing structure formed due to thermal shrinkage lifting during the late Yingcheng formation. Successive development in a pat- tern during the late Mingshui formation led to the formation of the primary gas pool. Vertical differential uplift during the late Nenjiang formation formed the Fulongquan structure during the late Paleogene. At this same time a secondary gas pool formed. A large scale reverse developed late in the Mingshui formation that provided the impetus for formation of a secondary gas pool. It is thought that the migration and accumulation of oil and gas was controlled by lithologic character, fracture, and structure. The local uplift in the vicinity of the hydrocarbon recession is most conducive to the collection of hydrocarbon gas.